Classroom management in the online environment: A case study of Thai TESOL staff in Thai university context - Kiatkheeree, Parussaya (Asian Journal of Education and Training, 2024)
The present pandemic has presented seriously affected not only the daily life but also teaching and learning and it has been seen a long battle for educators including TESOL teachers in Thailand. Working in the field of TESOL, the author experiences the new changing environment where an actual classroom turns into a virtual classroom. All documents and teaching tools prepared (before the pandemic) have been changed into online documents. Undeniably, online teaching can be seen as demanding as teaching staff moving from a space in which they have years of experience to the unknown world of online, remote, and socially distanced teaching. This study aims to identify Thai TESOL staff’s perception towards teaching and learning management affected by COVID-19. It The study revealed that the effectiveness of teaching in the changing context depends on the teachers’ readiness to a new learning technology like online meeting, at the same time, they must be open-minded and concerned that they must adjust their role to fit properly in the context. Even though participants found the significant change in the use of teaching technology in an online environment, interestingly their teaching and learning management remained as it used to be in the normal (onsite) classroom. In addition, the study provides implications for those who would like to create positive learning environment in online situation.